USE OF SERIOUS GAMES FOR THE ASSESSMENT OF MILD COGNITIVE IMPAIRMENT IN THE ELDERLY - CHOI, Moon-gee (Applied Computer Science, 2022)
This study investigated the use of computer games to detect the symptoms of mild cognitive impairment (MCI), an early stage of dementia, in the elderly. To this end, three serious games were used to measure the visio-perception coordination and psycho-motor abilities, spatial memory, and short-term digit span memory. Subsequently, the correlations between the results of the games and the results of the Korean Mini-Mental State Examination (K-MMSE), a dementia screening test, were analyzed. In addition, the game results of normal elderly persons were compared with those of elderly patients who exhibited MCI symptoms. The results indicated that the game play time and the frequency of errors had significant correlations with K-MMSE. Significant differences were also found in several factors between the control group and the group with MCI. Based on these findings, the advantages and disadvantages of using serious games as tools for screening mild cognitive impairment were discussed.